Bimbingan Rohani: Strategi Konseling Islam untuk Meningkatkan Religiusitas di Lingkungan Pesantren - Syaifatul Jannah; Ida (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
This research is guidance given to mahasantri in the form of Islamic religious values ​​so that they become true Muslim women. The purpose of this study was to find out how the implementation and results of Islamic spiritual guidance were applied to new mahasanti. The research method used in this study is the descriptive qualitative method because it wants to describe and describe what data is about the implementation of Islamic spiritual guidance to increase the religiosity of new mahasantri. While the data collection tools used the method of observation, interviews, and documentation. The subjects of this study consisted of two subjects, namely the cleric of the worship department and the new mahasantri of the intensive program at the Institute of Dirosat Islamiyah Al-Amien Prenduan. The results of the study show that Islamic spiritual guidance is provided in the form of spiritual guidance activities, namely: congregational prayers, prayer tasbih prayers, dzikir, tahajjud prayers, sunnah ba'diyah, and qobliyah prayers, and reading of the Qur'an. The method used is the ta'widiyah method (habituation), writing, mau'izhah (advice), demonstration, and imitation or Jibril. While the material used is in the form of faith. The results of the implementation of Islamic spiritual guidance are increasing faith and piety for new mahasantri, having an istiqamah attitude in carrying out Allah's commands, being able to take lessons from what is seen, increasing belief in Allah SWT, understanding the importance of religiosity for oneself and having the noble character in socializing